CASTE STRATIFICATION AND THE NARRATIVE OF UCHALYA: AN ANALYSIS OF LAXMAN GAIKWAD’S UCHALYA: THE BRANDED (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
The Book Uchalyas of Laxman Gaikwad and the Cast Stratification shown in the Book arediscussed in this article. Massive abuses of civil, political, economic, social, and culturalrights occur as a result of caste prejudice. It is frequently illegal in nations where it occurs,but due to a lack of enforcement and caste bias in the criminal system, victims are largelyunprotected. The book is the voice of those who have been marginalized and oppressed bymainstream Indian society, and who have been compelled to remain silent for a long time. Asa result, the article aims to investigate the nature of the Uchalya community's painful identityof being continually labeled as criminal, as well as the obstacles faced by the community as awhole in their daily lives. The British government has branded this group as criminal tribes.Finally, the book calls for the abolition of imposed social and legal limits, as well as socialjustice, rights, and many forms of reformation and transformation of the Uchalya community.